Company towns of the Pacific Northwest / Linda Carlson. - Carlson, Linda. (University of Washington Press, 2003)
"Company town." The words evoke images of rough-and-tumble loggers and gritty miners, of dreary shacks in isolated villages, of wages paid in scrip good only at price-gouging company stores, of paternalistic employers. But these stereotypes are outdated, especially for those company towns that flourished well into the twentieth century. In Company Towns of the Pacific Northwest, Linda Carlson provides a more balanced and realistic look at these "intentional communities."Drawing from residents’ reminiscences, contemporary newspaper accounts, company newsletters and histories, census and school records, and site plans, Carlson looks at towns in Oregon, Washington, and Idaho. She examines how companies went about controlling housing, religion, taxes, liquor, prostitution, and union organizers. This vibrant history gives the details of daily life in communities that were often remote and subject to severe weather. It looks at the tragedies and celebrations: sawmill accidents, mine cave-ins, and avalanches as well as Independence Day picnics, school graduations, and Christmas parties. Finally, it tells what happened when people left--when they lost their jobs, when the family breadwinner died or was disabled, when the mill closed.An ample selection of illustrations, most never previously published, broadens the appeal of this lively and well-researched book."--Back cover.